A Comparative Study of Profitability Analysis of Selected Listed Pharmaceutical Companies with Special Reference to Top 5 Pharma Companies in India - Rohan Jha (Management Journal for Advanced Research, 2023)
Profitability refers to the profits or gains a business makes in relation to its expenses. It helps to determine the future strategies of business, whether to invest or not and the performance of the business by analysing the currentfinancial position of the venture or firm. In this paper an attempt to assess the profitability position of selected pharma companies (on the basis of market capitalization). The annual report of last 5 years i.e. from 2018-19 to 2022-23 were analysed to know the position of pharma companies in terms of profitability. By analysing annual reports, it is found that among the selected pharma companies Sunpharma and Torrent Pharmaceutical are secured the top position (based on mean and C.V.) and in both based on mean and C.V. Cipla held the last position.